Faktor-Faktor Yang Mempengaruhi Keputusan Masyarakat Untuk Berdonasi Secara Online Melalui Platform Financial Technology Crowdfunding - Yulita Diyanti; Fathihani (CV ODIS, 2023)
Technological developments in the financial industry today provide many new innovations, one of the fintech-based technological innovations utilized is crowdfunding. This study aims to analyze the factors that influence people's decisions to donate online through the crowdfunding financial technology platform. The data used is primary data in the form of questionnaires distributed to 95 respondents selected using random sampling. This research uses the Theory of Planned Behavior (TPB). The results of this study indicate that religious factors, trust and convenience have a positive effect on online donation decisions